The application of pigment-protein fraction from Nannochloropsis oculata on β-actin response of Cromileptes altivelis infected with viral nervous necrosis - Uun Yanuhar; Achmad Khumaidi (Jurnal Akuakultur Indonesia)
ABSTRACT